2021
DOI: 10.1021/acs.jproteome.1c00636
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Infusion Start Time Mass Spectrometry Imaging of Dynamic SIL-Glutathione Biosynthesis Using Infrared Matrix-Assisted Laser Desorption Electrospray Ionization

Abstract: Due to the high association of glutathione metabolism perturbation with a variety of disease states, there is a dire need for analytical techniques to study glutathione kinetics. Additionally, the elucidation of microenvironmental effects on changes in glutathione metabolism would significantly improve our understanding of the role of glutathione in disease. We therefore present a study combining a multiple infusion start time protocol, stable isotope labeling technology, infrared matrix-assisted laser desorpt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…The heatmap of glutathione (GSH, [M-H] À = m/z 306.0765) abundance normalized to the abundance of homoglutathione (hGSH, [M-H] À = m/z 320.0922) measured by infrared matrix-assisted laser desorption electrospray ionization (IR-MALDESI)-MSI from a section of mouse liver was generated using the jet colormap and is shown in Figure 1A. 18 Homoglutathione was sprayed on the sample's microscope slide prior to sample mounting. The normalized GSH abundance is a relative quantification for GSH concentration within the tissue.…”
Section: Tutorialmentioning
confidence: 99%
“…The heatmap of glutathione (GSH, [M-H] À = m/z 306.0765) abundance normalized to the abundance of homoglutathione (hGSH, [M-H] À = m/z 320.0922) measured by infrared matrix-assisted laser desorption electrospray ionization (IR-MALDESI)-MSI from a section of mouse liver was generated using the jet colormap and is shown in Figure 1A. 18 Homoglutathione was sprayed on the sample's microscope slide prior to sample mounting. The normalized GSH abundance is a relative quantification for GSH concentration within the tissue.…”
Section: Tutorialmentioning
confidence: 99%
“…To address this issue, we have adapted a timed substrate infusion method, first described by Dudley et al, and later coined Multiple Infusion Start Times (MIST) by Paolini et al, that has been used in mass spectrometry analysis to provide detailed labeling kinetic data from a single tissue sample. Although not previously used with MSI, the MIST protocol is ideal for use in fMSI studies as a single tissue sample provides labeling data from multiple time points. Our study of mouse liver demonstrated that matrix-assisted laser desorption electrospray ionization (MALDESI) MSI can distinguish both the glycine isotopologue substrates and the glutathione products of metabolism . This method may likely be adapted to any system if multiple isotopologues of substrate molecules are available.…”
Section: Amino Acid Peptide and Protein Metabolismmentioning
confidence: 95%
“…Our study of mouse liver demonstrated that matrix-assisted laser desorption electrospray ionization (MALDESI) MSI can distinguish both the glycine isotopologue substrates and the glutathione products of metabolism. 36 This method may likely be adapted to any system if multiple isotopologues of substrate molecules are available. This work was performed with an orbitrap instrument allowing for high resolving power measurements, a key to measuring separate isotopologues.…”
Section: ■ Bioenergeticsmentioning
confidence: 99%
“…This can result in pixelated ion images making it difficult to delineate edges of histological features. To account for this, molecular standards with similar ionization efficiencies to the analyte of interest can be sprayed underneath biological samples and used for normalization 3–6 . However, normalization standards are difficult to choose for untargeted experiments because of the variability of ionization efficiencies between the molecules detected.…”
Section: Introductionmentioning
confidence: 99%
“…To account for this, molecular standards with similar ionization efficiencies to the analyte of interest can be sprayed underneath biological samples and used for normalization. 3 , 4 , 5 , 6 However, normalization standards are difficult to choose for untargeted experiments because of the variability of ionization efficiencies between the molecules detected. Many postprocessing normalization methods available do not require a standard to reduce the relative standard deviation between pixels/voxels.…”
Section: Introductionmentioning
confidence: 99%